Created vulnerabilities: political economy of tourism development in Sharm El Sheikh - Walsh, Catherine Meaghan (AUC Knowledge Fountain, 2020)
Sharm El Sheikh represents the typical tourism enclave: removed from the local culture and environment, homogenous with other destinations in the global south, and designed to serve the vacationing needs of mass tourism. This form of tourism development is dated and set to fail, particularly when challenged with political instability and violence. Literature on mass tourism to the global south focuses on structural dependency of resorts, but often fail to complicate this relationship with internal political decision making. This qualitative case study examines the development of the resort to cater to the desires of the mass tourism model. The socio-economic dependency of the space on the state and global tourism dynamics, the exclusion of the local population, and the complicated security crisis in the peninsula are analyzed as they remain significant challenges to future recovery of this resort.